Coblation of suprastomal granulomas in tracheostomy-dependent children. (May 2017) - Brown, C. Scott; Ryan, Marisa A.; Ramprasad, Vaibhav H.; Karas, Anatoli F.; Raynor, Eileen M.
Abstract: Objective: Suprastomal granulomas pose a persistent challenge for tracheostomy-dependent children. They can limit phonation, cause difficulty with tracheostomy tube changes and prevent decannulation. We describe the use of the coblator for radiofrequency plasma ablation of suprastomal granulomas in five consecutive children from September 2012 to January 2016. Method: Retrospective case series at a tertiary medical center. Results: The suprastomal granuloma could be removed with the coblator in all 5 cases. Three were removed entirely endoscopically and 2 required additional external approach through the tracheal stoma for complete removal. There were no intraoperative or postoperative complications. One patient was subsequently decannulated and 2 patients have improved tolerance of their speaking valves. Two patients remain ventilator dependent, but their bleeding and difficulty with tracheostomy tube changes resolved. Three of the patients have had subsequent re-evaluation with bronchoscopy, demonstrating resolution or markedly decreased size of the granuloma. This technique is time efficient, simple and minimizes risks associated with other techniques. The relatively low temperature and use of continuous saline irrigation with the coblator device minimizes the risk of airway fires. Additionally, the risk of hypoxia from keeping a low fractional inspiratory oxygen level (FIO2 ) to prevent fire is avoided. The concurrent suction in the device decreases blood and tissue displacement into the distal airway. Conclusion: Coblation can be used safely and effectively with an endoscopic or external approach to remove suprastomal granulomas in tracheostomy-dependent children. More studies that are larger and have longer follow-up are needed to evaluate the use of this technique.